The Self Control of Student in using of Social Media. - Desri Fitri Agung; Alizamar Alizamar; Afdal Afdal (Jurnal Aplikasi IPTEK Indonesia, 2020)
Self-control is the ability of self to control the urge to do or not do something that is desirable both in terms of acting and behaving, especially in the use of social media, self-control in the use of social media referred to in this study, namely behavioral control, cognitive control, and decision control. This study aims to describe self-control in the use of social media students of SMA Negeri 5 Padang. This research is a descriptive analysis study, with a sample of 276 students obtained using proportional stratified random sampling technique. The study used a questionnaire instrument compiled using a Likert scale model. The results of this study indicate that students of SMA Negeri 5 Padang in terms of behavior, cognitive and decision are in the high category and this certainly needs to be maintained so that students always control themselves in the use of social media so that students can focus more on learning both at home and at school .